Efektifitas Edukasi Model Kartu Pintar Deteksi Dini Risiko Preeklamsia (DEDI RAISA) Terhadap Peningkatan Pengetahuan Ibu Hamil - Fitriani Fitriani; Syahruni Syahruni (Media Kesehatan Politeknik Kesehatan Makassar, 2023)
Early detection plays a role in reducing maternal mortality and is very important. Morbidity and mortality of pregnant women can be prevented if pregnant women themselves are able to recognize the danger signs of pregnancy such as preeclampsia and try to seek help in health facilities, appropriate actions can prevent pregnant women from causing maternal death. This study aims to determine the effectiveness of the smart card education model of early detection of preeclampsia risk (dedi raisa) on increasing the knowledge of pregnant women. This study used a "quasi-experiment" design with a "Pretest-Posttest Control Group Design" approach. This study involved 90 pregnant women who checked their pregnancy at Kassi - Kassi Health Center and Bara - Baraya Health Center Makassar from August to October 2023. Samples were selected through purposive sampling technique. Statistical analysis used in this study is the Wilcoxon test. Based on the results of the Wilcoxon statistical test, the p value = 0.000 indicates that education using the smart card model is effective in increasing the knowledge of pregnant women regarding early detection of preeclampsia risk. From the pre-test results, most of the pregnant women respondents did not know well about early detection of preeclampsia that could occur in pregnant women. This shows that information about preeclampsia and how to do early detection, has not been widely understood by pregnant women in the Kassi - Kassi health center area and the Bara - Baraya Makassar health center, after providing education with the Dedi Raisa Smart Card method and conducting a post test, there was an increase in the knowledge of pregnant women related to early detection of preeclampsia.